Analisis Minat Belajar Matematika Berbasis Daring Pada Siswa Sekolah Dasar Di Kelas Rendah - Dhea Nada Oktavia; Astri Sutisnawati; Luthfi Hamdani Maula (STKIP Andi Matappa Pangkep, 2020)
This study aims to analyze the online mathematics learning interest of students in grade 3.2 at SDN Suryakencana CBM. This type of research uses a basic theory study approach with a qualitative descriptive method, because in examining problems regarding the interest in learning mathematics online. In practice, it uses interview guidelines and documentation of student interviews to find out the extent of interest in online-based mathematics learning. The research subjects used Quota Sampling, because the subjects studied were groups that had been determined according to the quota in class 3.2 SDN Suryakencana CBM. The results obtained from this study were to determine how students' interest in learning mathematics based online, in practice the teacher applied various methods and strategies in the form of making videos with concrete objects in order to make it easier for students when the learning process took place at home online. However, there are some students who do not understand when the online-based learning process takes place, which is sent by the teacher via the WhatsApp application, because the learning is ineffective and the lack of support from the students 'parents has reduced students' interest in learning mathematics in grade 3.2 SDN Suryakencana CBM.